Impact of anastomotic leakage and radiotherapy on long-term quality of life after sphincter-saving rectal resections - Khalilov, Rasim; Seyfried, Steffen; Reißfelder, Christoph; Hardt, Julia; Herrle, Florian; Yagublu, Vugar (Langenbeck's archives of surgery, 2025)
Background The impact of anastomotic leakage (AL) on quality of life (QoL) following low anterior resections (LAR) remains a pressing concern, particularly as advancements in surgical techniques and multimodal treatments have resulted in an increasing number of survivors. Methods This study evaluated how AL affected health-related QoL in patients treated at the Department of Surgery, University hospital Mannheim of Heidelberg University from 2010 to 2021, utilizing the LARS score, the EORTC QLQ-C30, and the EORTC QLQ-CR29 questionnaires. Results The study included 20 patients in each group, with those having AL matched 1:1 to control subjects without AL, based on criteria such as age, gender, comorbidities, tumor location, and resection degree. Both groups showed impaired QoL in EORTC assessments, with no statistically significant differences except in the abdominal pain scale of EORTC QLQ-CR29, which was higher for AL patients (19.99 ± 22.68 vs. 6.66 ± 17.43; p = 0.03). Comparison of QoL between patients who received neoadjuvant radiotherapy and those who did not, independent of AL, revealed significantly reduced QoL in several scales of both the EORTC QLQ-C30 and QLQ-CR29 assessments. A statistically significant worsening of QoL was observed in the sore skin domain (36.66±34.81 for RT vs. 3.70±11.11 without RT; p = 0.02) of the EORTC QLQ-CR29 among AL patients who received neoadjuvant radiotherapy. AL patients treated with Endoscopic Vacuum Therapy (EVT) showed improved QoL. Conclusions AL alone does not appear to be an independent risk factor for impaired QoL after LAR for rectal cancer. However, the combined effect of AL and neoadjuvant radiotherapy may contribute to worse functional outcomes, significantly impacting QoL. Effective AL management with EVT can help mitigate these effects and improve patient outcomes.